2008
DOI: 10.1038/sj.jhh.1002320
|View full text |Cite
|
Sign up to set email alerts
|

Home blood pressure measurements associated with better blood pressure control: the J-HOME study

Abstract: The usefulness of self-measurements of blood pressure (BP) at home (home BP measurements) in hypertensive patients has been reported by many studies. Several national guidelines recommend the use of home BP measurements to achieve better hypertension control. The objective of this study was to clarify the association between home BP measurements and hypertension treatment among 2363 essential hypertensive patients taking antihypertensive drugs. Compared to the 543 (23.0%) patients who had not taken home BP mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…The first notable observation provided by this study is that the proportion of patients measuring HBP in a Japanese primary care setting is similar to, 15 or even higher 14 than, that reported by European specialist settings; this difference may result from a more careful management of hypertension in that country, as reflected by the high degree of clinic BP control (440%) reported in the present study. The second interesting finding of the study by Obara et al 12 , which confirms and extends previously published data, is that BP control was better among patients practising HBP either in the office or outside the office environment. This observation adds a new piece of information over previous reports investigating the role of HBP compared to office BP measurement in BP control.…”
Section: Hbp and Bp Controlsupporting
confidence: 87%
See 4 more Smart Citations
“…The first notable observation provided by this study is that the proportion of patients measuring HBP in a Japanese primary care setting is similar to, 15 or even higher 14 than, that reported by European specialist settings; this difference may result from a more careful management of hypertension in that country, as reflected by the high degree of clinic BP control (440%) reported in the present study. The second interesting finding of the study by Obara et al 12 , which confirms and extends previously published data, is that BP control was better among patients practising HBP either in the office or outside the office environment. This observation adds a new piece of information over previous reports investigating the role of HBP compared to office BP measurement in BP control.…”
Section: Hbp and Bp Controlsupporting
confidence: 87%
“…In contrast to Japan Home versus Office BP Measurement Evaluation data, previous studies have shown that hypertension management based on HBP targets is associated with less intensive therapeutic regimens in the office as well as outside the office BP control. 19,21 Despite the documented value of HBP in improving medical management and patients' compliance, prospective studies are needed to confirm or refute the findings by Obara et al 12 and to establish whether and how HBP is an effective way for improving BP control in the hypertensive population. The interest in this field is evident by the increasing literature on this topic-even in this journal [22][23][24] -in relation to uptake and implications of home HBP measurements.…”
Section: Hbp and Bp Controlmentioning
confidence: 97%
See 3 more Smart Citations